Evaluation of the Implementation of the Smoking Cessation Clinic at Padang Karambia Health Center, Payakumbuh City - Rahmi Kurnia Gustin (Journal of health research and technology, 2025)
The smoking cessation clinic was inaugurated in 2012 at the Puskesmas Padang. Based on clinical register data, the number of patients from 2016 to 2018 continues to decline. This study aims to determine the implementation of the smoking cessation clinic at the Padang Karambia Health Center, Payakumbuh City in 2021. This type of research uses qualitative research which was conducted from February to March 2021 in the Padang Karambia Health Center Work Area. The samples taken were 11 people as informants with purposive sampling technique. Data collection was carried out by in-depth interviews, FGDs, review of documents and observations. The data is processed through data reduction, data presentation, and drawing conclusions, after which triangulation is carried out. The results showed that from the point of view of smoking cessation clinics have staff as officers but have other duties, there is no financial support for the program and no special rooms, the Standard Operating Procedure (SOP) already exists but has not been evaluated and revised. In terms of the process, the socialization was not optimal, there was identification of kilien, counseling and therapy 3 times a week, the follow-up was not going well. There is no measurable activity achievement target and patient visits are still very low. In 2020 there were no patient visits due to the Covid-19 Pandemic, while in 2019 the number has decreased from the previous year. This is due to the lack of socialization / promotion activities due to the absence of a supporting budget, as well as a lack of motivation for smokers to visit. For this reason, the Puskesmas Padang Karambia should allocate funds to support smoking cessation clinical activities so as to increase socialization / promotion. Keywords : Evaluation, Implementation, Smoking Cessation Clinic